1965
DOI: 10.1111/j.2042-7158.1965.tb07696.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriostatic actions of some tetracyclines

Abstract: 6-Demethyl-6-deoxytetracycline, 6-methyleneoxytetracycline, 7-chlortetracycline and 7-chlor-6-demethyltetracycline inhibit Aerobncter aerogenes in glucose-mineral salt media, by two modes of action, I and 11, shown by tetracycline and oxytetracycline (Jones & Morrison, 1962;1963) : Mode I1 by 6-demethyl-6-deoxytetracycline is not detected by inhibition of growth of the organism but by inhibition of the anaerobic consumption of pyruvate which is also a consequence of Mode 11. The chlorinecontaining tetracycline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1967
1967
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Tetracyclines are bacteriostatic agents with broad-spectrum antimicrobial activity (3). Doxycycline is a semisynthetic, longacting, second-generation tetracycline which is absorbed rapidly and penetrates well into the brain and CSF (48).…”
mentioning
confidence: 99%
“…Tetracyclines are bacteriostatic agents with broad-spectrum antimicrobial activity (3). Doxycycline is a semisynthetic, longacting, second-generation tetracycline which is absorbed rapidly and penetrates well into the brain and CSF (48).…”
mentioning
confidence: 99%
“…Mode II inhibition, under aeration conditions, is considered a derangement of protein synthesis. Subsequently, BENBOUGH and MoRRISON (1965) proposed a third mode of action for the chlorinated derivatives related to the metabolism of D-glutamate (see also SNELL and CHENG, 1961). (also see HAHN, 1959 and demonstrated that the effects of mixtures of chloramphenicol and either OTC or CTC on the growth rate of E. coli were additive.…”
Section: Protein Synthesismentioning
confidence: 98%
“…Some authors suppose that their primary site of action is the bacterial synthesis of proteins (HAHN 1960, FRANKLIN andGODFREY 1965). Others think that electron transfer and energy yielding metabolism are the first reaction inhibited owing to the structural pecularities of the tetracyclines (SAZ andMARTINEZ 1958, PLAKUNOV 1964, GRUNERTOVA 1964, BENBOUGH andMORRISON 1965).…”
mentioning
confidence: 99%